1977
DOI: 10.1029/jb082i020p02945
|View full text |Cite
|
Sign up to set email alerts
|

Seismic moments of major earthquakes and the average rate of slip in central Asia

Abstract: Seismic moments for 12 major

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
141
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 300 publications
(154 citation statements)
references
References 22 publications
9
141
1
2
Order By: Relevance
“…We therefore have chosen to retain the original body-wave magnitudes during inversion. For the largest event in the catalog, the 1950 Chayu earthquake in eastern Assam, we use the hypocentral location and magnitude listed in Chen and Molnar (1977).…”
Section: Methodsmentioning
confidence: 99%
“…We therefore have chosen to retain the original body-wave magnitudes during inversion. For the largest event in the catalog, the 1950 Chayu earthquake in eastern Assam, we use the hypocentral location and magnitude listed in Chen and Molnar (1977).…”
Section: Methodsmentioning
confidence: 99%
“…There appears to have been no major (M . 7.6) earthquakes since at least 1911 along the Altyn Tagh Fault (Chen & Molnar 1977). A traverse across the Altyn Tagh Fault and Kun Lun by Molnar et al (1987a,b) revealed evidence for relatively recent faulting from 10 m offset ridges and fresh mole tracks 0.4 m high, the freshness of which they considered to point to an earthquake in the last few hundred years.…”
Section: Earthquake Historymentioning
confidence: 99%
“…Kayal (figures 9 and 12 (b)). Chen and Molnar (1977), however, based on first motion data, determined a thrust faulting solution. Armijo et al (1989) preferred the strike slip solution of the 1950 earthquake interpreting the right-lateral strike-slip on the Po Qu fault zone in southeast Tibet, which wraps around the eastern syntaxis and connects with the right-lateral strike-slip Sagaing fault zone ( figure 12(b)).…”
mentioning
confidence: 99%